Prediksi Angkutan Sedimen Melayang pada Sungai Bolango Di Provinsi Gorontalo - Chiquitha Puspitha Puteri Olii; Komang Arya Utama; Rawiyah Husnan (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Bolango River is a river that has potential as a source of raw water and irrigation for communities in Gorontalo Province. Sedimentation in the upstream and downstream of the river causes a decrease in river function. This research aims to predict the amount of suspended sediment transport discharge in Bolango River which is compared with the results of calculations using empirical methods. The calculation method used is the calculation of the instantaneous method (USBR) which is compared with three empirical methods namely Einstein, Lane and Kalinske, and Chang, Simon and Richardson by taking sediment samples and measuring river hydrometry. Based on the results of the calculation of the amount of drift sediment transport in Bolango River with the instantaneous method (USBR) ranged from 13,039-158,028 tonnes/year, Lane and Kalinske approach 26,013-253,138 tonnes/year, Einstein approach ranged from 12,458-50,350 tonnes/year and Chang, Simons & Richardson approach ranged from 1,598-19,257 tonnes/year. The closest comparison result to the instantaneous method (USBR) is the Lane and Kalinske approach with a percentage of 99.6% in the upper reaches of the river, 105.33% in the middle reaches, and 60.18% in the lower reaches.